Transactivation of the EGF receptor as a novel desensitization mechanism for G protein-coupled receptors, illustrated by dopamine D2-like and β2 adrenergic receptors - Kundu, Dooti; Min, Xiao; Wang, Shujie; Peng, Lulu; Tian, Xinru; Wang, Mengling; Kim, Kyeong-Man (Cellular & molecular biology letters, 2024)
Transactivation of epidermal growth factor receptors (EGFR) provides intricate control over multiple regulatory cellular processes that merge the diversity of G protein-coupled receptors (GPCRs) with the robust signaling capacities of receptor tyrosine kinases. Contrary to the typical assertions, our findings demonstrate that EGFR transactivation contributes to the desensitization of GPCRs. Repeated agonist stimulation of certain GPCRs enhanced EGFR transactivation, triggering a series of cellular events associated with GPCR desensitization. This effect was observed in receptors undergoing desensitization (D 3 R, K149C-D 2 R, β 2 AR) but not in those resistant to desensitization (D 2 R, C147K-D 3 R, D 4 R, β 2 AR mutants lacking GRK2 or GRK6 phosphorylation sites). The EGFR inhibitor AG1478 prevented both desensitization and the associated cellular events. Similarly, these cellular events were also observed when cells were treated with EGF, but only in GPCRs that undergo desensitization. These findings suggest that EGFR transactivation diversifies pathways involved in ERK activation through the EGFR signaling system and also mediates GPCR desensitization. Alongside the widely accepted steric hindrance model, these findings offer new insights into understanding the mechanisms of GPCR desensitization, which occurs through complex cellular processes.